Conservation Genomics of Cascades Frogs (Rana cascadae) at the Southern Edge of Their Range - (:unkn) unknown (My University, 2018)
Cascades frogs (Rana cascadae) in the southern Cascades Range of California have been declining over the last 30 years, primarily due to the fungal pathogen, Batrachochytrium dendrobatidis (Bd). In the Lassen Region of the southern Cascades, at least six of the eleven remaining localities face extirpation within 50 years. These small and isolated populations are prone to negative genetic effects including reduced diversity and increased inbreeding which could potentially exacerbate declines. I used a large dataset of SNP loci generated from high-throughput sequencing to characterize patterns of genetic structure and diversity in twelve R. cascadae populations in California to prioritize populations for conservation and compared these populations with three in Oregon to determine differences in diversity and population divergence. I also detected outlier loci using genome-scan methods and compared patterns of differentiation between these loci and presumably neutral loci. I found evidence of genetic structure in California creating two main groups of ancestry despite a strong pattern of isolation-by-distance (IBD), with Oregon populations forming a third group. Populations in California were highly differentiated from those in Oregon and had lower estimates of genetic diversity that support documented demographic declines. Rana cascadae was also moderately differentiated between the two main regions within California but genetic diversity was similar. Patterns of genetic differentiation were overall similar between outlier and neutral loci. These findings indicate that Cascades frogs in California should be managed by genetic ancestry and not by ecoregion, as they are currently. Source populations should be selected by choosing the nearest and demographically largest site to the donor population within the same major genetic ancestry group to maximize genetic diversity and minimize both outbreeding and inbreeding depression. This study provides the beginnings for understanding the spatial genetic structuring of Cascades frogs in California and provides managers a way forward for active conservation in the face of ongoing declines.